SEAPOP studies in the Lofoten and Barents Sea area in 2005 - Anker-Nilssen, Tycho; Barrett, Robert T.; Bustnes, Jan Ove; Erikstad, Kjell E; Fauchald, Per; Lorentsen, Svein Håkon; Steen, Harald; Strøm, Hallvard; Systad, Geir Helge Rødli; Tveraa, Torkild (Norsk institutt for naturforskning, 2006)
This is the first annual report from SEAPOP, a long-term seabird programme aiming to provide and maintain base-line knowledge needed for an improved management of marine areas. For several reasons, the activities in the initial year were restricted to the Lofoten and Barents Sea area, but the programme is designed for implementation on the full national scale within a few years. The report presents briefly some important results from the investigations made in 2005 and some leading principles for how data and knowledge will be organised and served to different users online via a SEAPOP web site. The monitoring of population trends, reproduction, adult survival rates and diet of selected seabirds species on the previously established key-sites Røst, Hjelmsøya, Hornøya and Bjørnøya was extended and further adjusted to meet the general design of the programme. In addition, two new key-sites were established, one on Anda in Vesterålen and the other on western Spitsbergen. The latter was divided among several localities because there is no suitable single site in the area that holds a sufficient variety of breeding species. For each keysite, the report presents a table listing the main results from the monitoring in 2005. On the basis of time series that date back many years, a number of interesting trends for different species and parameters were uncovered, both within and between the colonies. Some selected topics are treated in more detail in separate text boxes, which also present a few technological advances and statistical challenges for monitoring design. The work in 2005 represented a new initiative for the mapping of seabirds in Norway’s northernmost areas, and included an updating survey of breeding seabirds in the Isfjorden area on Spitsbergen and along the entire coastline of Troms and Finnmark counties east to Laksefjorden. Studies of seabirds at sea were continued through participation on several ecosystem surveys led by the Institute of Marine Research. The data analyses were aimed at developing ...